Sistem Penunjang Keputusan Metode Simple Additive Weighting Untuk Penentuan Penerima Beasiswa Pada MA Al-Mukhlishin Ciseeng - Abdoel Kadir Zaelani; Mochammad Bagoes Satria Junianto (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Education is one of the most basic human rights, both for those who are able or those who cannot. By getting a good and proper education, there will be opportunities to get a better life for them. To support the 12 year compulsory education program, the government provides free education programs and scholarship programs. Scholarships can be said to be assistance for the ongoing education provided by the government, private companies, embassies, universities, foundations, as well as educational institutions or researchers. Likewise with the MA Al-Mukhlishin as one of the formal educational institutions, the scholarship program must be awarded to those who are entitled to receive it, especially based on the scholarship recipient's classification, quality and competence. So we need a Decision Support System (DSS) that can help the selection team in facilitating the selection process for scholarship recipients based on the specified criteria. The method used in this research for the scholarship recipient's decision support system is the Simple Additive Weighting (SAW) method. This method was chosen because this method determines the weight value for each attribute, then it is followed by a ranking process that will select the best alternative from a number of alternatives. The programming language used in building this system is Java, using the Netbeans compiler. The system development method used by the author in this study is the waterfall method which has 5 stages, namely planning, analysis, design, implementation, and maintenance.